Pelatihan Pembuatan Burger Sehat menggunakan Oatmeal Kepada Masyarakat Perumahan Villa Mas Indah - Miftahudin; Cindy Naomi Nainggolan (Bulletin of Community Engagement, 2024)
Consumption of healthy food has become an essential need in efforts to improve the quality of public health. This training on making healthy burgers using oatmeal was conducted with the aim of providing understanding and skills to the residents of Villa Mas Indah housing complex about healthy food alternatives based on oatmeal. Oatmeal, which is rich in fiber and nutrients, was chosen as the main ingredient in making the burgers as an effort to reduce the consumption of saturated fats and increase daily fiber intake. The training methods included the introduction of oatmeal's benefits, a burger-making demonstration, and interactive sessions for participants. The evaluation results showed that participants experienced a significant increase in knowledge about healthy food and practical skills in preparing healthy meals. This training is expected to contribute to a healthier lifestyle for the community and serve as a model for community-based healthy food development